2008
DOI: 10.1088/0957-4484/19/40/405503
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-based synthesis of porous zinc ferrite nanorods and its application in a room-temperature ethanol sensor

Abstract: Porous zinc ferrite (ZnFe(2)O(4)) nanorods with a diameter of around 50 nm and a length of several micrometers have been synthesized by a microemulsion-based method in combination with calcination at 500 °C. The morphology and structure of the ZnFe(2)O(4) nanorods and its precursor (ZnFe(2)(C(2)O(4))(3) nanorods) were systematically characterized by x-ray powder diffraction, transmission electron microscopy, field emission scanning electron microscopy and high-resolution transmission electron microscopy. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…2a as-prepared Co 3 O 4 nanorods. During the whole calcination process, it could be seen that the product Co 3 O 4 nanorods retained its original rod-like morphology of their precursor CoC 2 O 4 In other words, this growth process can be regarded as a morphologically templated nucleation process [29][30][31]. The asprepared Co 3 O 4 nanorods with diameter of 150-250 nm and length of 3-5 mm are straight (Fig.…”
Section: Electrochemical Properties Of Co 3 O 4 Nanorodsmentioning
confidence: 90%
“…2a as-prepared Co 3 O 4 nanorods. During the whole calcination process, it could be seen that the product Co 3 O 4 nanorods retained its original rod-like morphology of their precursor CoC 2 O 4 In other words, this growth process can be regarded as a morphologically templated nucleation process [29][30][31]. The asprepared Co 3 O 4 nanorods with diameter of 150-250 nm and length of 3-5 mm are straight (Fig.…”
Section: Electrochemical Properties Of Co 3 O 4 Nanorodsmentioning
confidence: 90%
“…For these applications the surface morphology of ZnFe 2 O 4 plays a vital role to tune their chemical and physical properties to the appropriate ones. Nowadays, various ZnFe 2 O 4 nanostructures such as nanoparticles, nanotubes, nanosheets, nanoflowers and nanowalls are widely used in the fabrication of various devices [18][19][20][21][22] Gas sensing properties of zinc ferrite are already reported in the literature for nanopowders [23], thick and thin films [17][18][19], nanorods [20], core-shell microspheres [21] and nanotubes [22]. Li et al [24] reported the synthesis of spinel zinc ferrite nanospheres having diameter $212 nm via a general, one-step and template-free solvothermal route.…”
Section: Introductionmentioning
confidence: 99%
“…Sutka et al [26] presented an easy development of cheap, sensitive and integrable spinel zinc ferrite thin film gas sensors for the detection of ethanol. Thus most of the studies reported in the literature present the sensing response at relatively high temperatures [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, ferrite, an iron oxidebased mixed metal oxide, has been extensively studied due to its unique properties [3]. As a typical ferrite spinel (AFe 2 O 4 ; A = Mn, Zn, Co, Ni, Cd), zinc ferrite (ZnFe 2 O 4 ) has received great interests due to its significant applications in photocatalysis, information storage, electronic devices, magnetic materials and gas sensing [4,5]. In recent years, many efforts have been devoted to synthesize ZnFe 2 O 4 nanomaterials.…”
Section: Introductionmentioning
confidence: 99%